Optimization Of Boiler Feedwater Treatment Through Varies Softener Regeneration Process Inlet Pressure - Mohammad, Aiman Aminuddin; Kasmin, Ashari (Progress in Engineering Application and Technology, 2023)
Water softener are the common method for treating the properties of boiler feedwater from hard water to soft water. Hard water contains unwanted properties that can scale up the internal components of a boiler and it will result in reducing the heat exchange efficiency and cause scaling and corrosion problem inside the boiler. This project is focused on the boiler incoming feedwater that located in Bio-diesel laboratory at Universiti Tun Hussein Onn Malaysia (UTHM). This project objectives are to perform softener regeneration process i.e., backwash, charge and rinse process through five different stages of flowrate within five weeks of experiment. The variable that has been measured for softener water quality test is pH value and the total hardness. Water softener must be regenerate according to the guideline that have been set by Universiti Tun Hussein Onn Malaysia (UTHM) Biodiesel Plant. In order to obtain the best water quality, it is important to maintain the water treatment performance through the softener regeneration process. In this experiment, the suitable amount of flowrate has been identified after five different stage of flowrate testing and the water quality test have been conducted. Next, student have analyzed boiler water treatment test i.e., sulphate test, hydrate alkalinity test and pH test using BP 100 and BP 210 chemicals. From the analysis, the suitable chemical dosage for boiler water treatment has also been determined. This project is important to ensure that the quality of boiler water is comply with the guideline that have been set by Universiti Tun Hussein Onn Malaysia (UTHM) Biodiesel Plant to prevent scaling and corrosion to form inside the boiler. In conclusion, this project can be as a reference in the future for the softener regeneration process guideline.